The Role of Decision Support System and Risk Management Using Social Media Promotion - Sulastri, Lilis; Novitasari, Deltari; Rahmaningtyas, Wisudani; Sulaeman, Ridawati; Erlangga, Heri (International Journal of Psychosocial Rehabilitation, 2020)
In this paper critique was to construct a framework of reference for the utilization of social networks as a decision support systems tool for the efficiency of very little and medium enterprises. Twenty analysis articles were review from 2011 to 2017 that associated with the topics of decision support systems, strategic alternatives, and social networks. The analysis findings counsel that the utilization of decision support systems facilitates the organization gain a competitive advantage, improve performance by analyzing the knowledge obtained, and conjointly the knowledge extracted from social networks add value to the company with low investment. Social networks have reworked the availability of information for his or her customers, making gettable a bunch of tools for wanting, debugging, and substantiating info from both: individuals and organizations. The utilization of social media is Associate in nursing economical modality for the event of relationships with purchasers and employees. The study its integration for structure functions. What is additional, our study multiple establish the ascent background among the, the use of social media for knowledge sharing throughout necessary events. There by any analysis in social media analysis perceive. Many studies have viability of investigated the on-line community. Equally as for seeking and rendering facilitate has to boot been investigate in previous analysis. Completely different contexts embrace political and social media a promoting medium, whereas others have explored varied aspects of social media. Public administration and also the comparison between ancient and social media.